DISTINCTIVE FEATURES OF THE CRIME OF GENOCIDE FROM SIMILAR CRIMES COMMITTED AGAINST ETHNIC GROUPS - Габібова, Кенуль Абульфазкизи (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Objective: to consider the crime of genocide against ethnic groups, its characteristics, as well as the closest to him (and often confused) concept of ethnic cleansing, which have similar and distinctive features. Research methods: historical, comparative legal. Results: a legal assessment of the results of the genocide as the most brutal among crimes committed against the world and humanity. In addition, the definition of forced relocation, deportation and exile was clarified. The importance of the article lies in the fact that the author tries to explain in which cases forced relocation is closest to ethnic cleansing, in which cases it should be considered a crime of genocide. Discussion of the problem: the term genocide, after it became known to legal science, created the concept of ethnic cleansing. Although these concepts are known to us from the last century, the events covered by them have been committed since ancient times. But the legal assessment of their results began from the last century. The UN Convention on the Prevention of the Crime of Genocide and its Punishment recognized only four protected groups, and the reason is related to the stable structure of these groups. Of these groups, national, ethnic, racial groups are stable, with a stable character of religious groups there are always controversial opinions. Because a person at birth cannot choose religious affiliation, he further understands the meaning of religion and religion, and at this time can change religion. Therefore, the stable nature of religious groups is a controversial issue. In connection with the protection of the international convention on the genocide of ethnic groups, it should be noted that in the modern period the concept of nationality is identified with the concept of citizenship. This feature is mainly developed and shows itself in the countries of North America and Europe. From this point of view, if a nation and citizenship have the same content, then the existence of a nation is directly proportional to the existence of citizenship. In the absence of a state there can be no nation, just as the question of citizenship comes up. But people can exist and continue to live without a state (as exemplified by the Gypsies). And how can groups without a state be defended? This issue is related to ethnicity. Therefore, nations that do not have a state are protected by the Convention and are called ethnic groups.